PELATIHAN DESAIN KEMASAN PRODUK UNTUK MENARIK MINAT KONSUMEN - Mesra Surya Ariefin; Mu'ah Mu'ah; Mesra Berlyn Hakim; Aranta Prista Dilasari (Bajang Institute, 2025)
The Product Packaging Design Training to Attract Consumer Interest in Lamongan,Jawa Tengah, aims to enhance the understanding and skills of SMEs in designing effective and attractive packaging. This training includes an introduction to the importance of packaging from marketing, branding, and consumer psychology perspectives, as well as the basic principles of packaging design such as color, typography, layout, and visuals. Participants are also given the opportunity to join a packaging design workshop, where they can create their own design concepts with guidance from facilitators and use simple design software. Additionally, participants are taught how to select the right packaging materials, considering functionality, sustainability, and production costs. The simulation and evaluation session allows participants to receive feedback and make improvements to their designs. At the end of the training, participants will prepare a follow-up plan to implement their packaging designs in their businesses, aiming to enhance product appeal and consumer interest.